Analysis of the Menstrual Cycle Variabilities of the Human Epididymis Protein 4 - Nikolova, T; Živadinović, R; Nikolova, N; Evtimovska, N; Pavlovski, B; Tofiloska, V (Faculties of Medical Sciences, The University of the West Indies, Mona Campus, Kingston, Jamaica, St. Augustine Campus, Trinidad and Tobago and Cave Hill Campus, Barbados., 2016)
Epididymis Protein 4 (HE4) serum levels in women with benign ovarian diseases. A prospective study was done at the University Clinic of Obstetrics and Gynaecology in Skopje. Ninety-four patients divided into two groups: 37 patients with ovarian endometriosis and 57 patients with the “other benign pelvic masses” were included in the study. After the ultrasound finding of a pelvic mass with a possible ovarian origin, all the patients were serum sampled for HE4 and carbohydrate antigen-125 (CA125). All the cases underwent surgical removal of the mass with subsequent histologic evaluation which was referent for the group classification. There were no significant differences in the HE4 in the blood levels between the follicular (FP) and the luteal phases (LP) in the patients with ovarian endometriosis (t35 = 0.147, p = 0.884) and the “other benign pelvic masses” (U = 424.5, p = 0.730). There were no significant differences in the HE4 serum levels in the follicular phase between the two groups (U = 222.0, p = 0.266) and in the luteal phase. The difference in the HE4 serum levels between the two groups (Mdn 40.20 vs 35.50 pmol/L), U = 469.5, p = 0.048, was statically significant. Hence, HE4 is a robust biochemical marker and could be tested irrespective of the variations in the menstrual cycle
Keywords: Human Epididymis Protein 4 (HE4); menstrual cycle; variability